A placebo-controlled, parallel-group, randomized withdrawal study of subjects with symptoms of spasticity due to multiple sclerosis who are receiving long-term Sativex® (nabiximols) - Notcutt, W; Langford, R; Davies, P; Ratcliffe, S; Potts, R (Multiple sclerosis, 2012)
Background: Open-label studies are not ideal for providing robust evidence for long-term maintenance of efficacy of medicines, especially where medicines provide symptom relief and where long-term use of a placebo may be problematic and not ethical. Objective: To evaluate the maintenance of efficacy of Sativex in subjects who have gained long-term symptomatic relief of spasticity in multiple sclerosis (MS), and to assess the impact of sudden medicine withdrawal. Methods: An enriched enrolment randomized withdrawal study design was used. Eligible subjects with ongoing benefit from Sativex for at least 12 weeks entered this 5-week placebo-controlled, parallel-group, randomized withdrawal study. Each subjects’ previous effective and tolerated dose was continued. Results: A total of 18 subjects per group were enrolled. Demographics showed a mean duration of MS of 16.4 years, spasticity 12.7 years, mean duration of Sativex use of 3.6 years (median 3.4 years) and a mean daily dose of 8.25 sprays. Primary outcome of time to treatment failure was significantly in favour of Sativex (p = 0.013). Secondary endpoints showed significant changes in the Carer and Subject’s Global Impression of Change scales in favour of Sativex. Conclusions: Maintenance of Sativex efficacy in long-term symptomatic improvement of spasticity to a group of subjects with MS has been confirmed using this study design.